1999
DOI: 10.1557/s1092578300000661
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Growth of Gallium Nitride by the Chemical Vapor Reaction Process (CVRP)

Abstract: A new process for synthesis and bulk crystal growth of GaN is described. GaN single crystal c-plane platelets up to 9mm by 2mm by 100 µ m thick have been grown by the Chemical Vapor Reaction Process (CVRP). The reaction between gallium and a nitrogen precursor is produced by sublimation of solid ammonium chloride in a carrier gas, which passes over gallium at a temperature of approximately 900 ° C at near atmospheric pressures. Growth rates for the platelets were 25-100 µ m/ hr in the hexagonal plane. Seeded g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Anhydrous ammonia was condensed (at À196 1C) into a 8 mm OD/4 mm ID or a 8 mm OD/5 mm ID quartz tube containing GaN and any salt additives, and the tube was flame-sealed at a height as noted in Table 1. Most of the source h-GaN was obtained from a chemical vapor reaction process [11]. The tubes were heated in a pressurized hydrothermal system and the products were isolated in a manner identical to that reported previously [1,3,4,9].…”
Section: Ammonothermal Reactions In Quartz Tubesmentioning
confidence: 99%
“…Anhydrous ammonia was condensed (at À196 1C) into a 8 mm OD/4 mm ID or a 8 mm OD/5 mm ID quartz tube containing GaN and any salt additives, and the tube was flame-sealed at a height as noted in Table 1. Most of the source h-GaN was obtained from a chemical vapor reaction process [11]. The tubes were heated in a pressurized hydrothermal system and the products were isolated in a manner identical to that reported previously [1,3,4,9].…”
Section: Ammonothermal Reactions In Quartz Tubesmentioning
confidence: 99%
“…Argoitia et al [9] demonstrated that molten Ga reacts with atomic nitrogen to form a thick crust of polycrystalline GaN. This paper reports an improvement to the previous processes [7][8][9] using ammonia for low cost commercial production of polycrystalline nitride bulk material. Synthesis of highpurity, dense polycrystalline GaN was accomplished.…”
Section: Introductionmentioning
confidence: 87%
“…In 1999 we reported a new process called the chemical vapor reaction process (CVRP) to synthesize gallium nitride [7] and to manufacture nitride targets for use in sputtering and similar equipment [8]. All GaN obtained by these processes, however, are either small needles or powder agglomerations of low density, which require high-temperature and high-pressure sintering to produce high-density polycrystalline bulk for source material.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical vapor reaction process (CVRP), which was first proposed for GaN growth by Callahan et al [15] is one of the candidates to achieve high A1N growth rates. In the case of GaN, the growth rate has reached 100 mm/h.…”
Section: Introductionmentioning
confidence: 99%